STUDY SOURCES OF THE ELECTROMAGNETIC FIELD OF THE HIGH-HIGH FREQUENCY RANGE FOR THE TREATMENT OF SOWS WITH MASTIT-METRIT-AGALACTIA SYNDROME - Mikhailova , L.M.; Dumanskyi , O.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The article proposes to investigate highly stable sources of the electromagnetic field of the ultrahigh frequency range for the treatment of animals, in particular sows with mastitis-metritis-agalactia syndrome. To create electrical technologies related to the influence of EMF on biological objects, research is needed to create highly stable microwave EMF sources that meet high requirements for the spectrum of output signals, the range of frequency adjustment and power of the output signal.In the treatment of sows with metritis-mastitis-agalactia, radiation sources in the range of 141 ... 143 GHz with an output power level of at least 250 mW, frequency instability of the order of 10-6 ... 10-7, phase noise level - 90 are required. .. 100 dB / Hz at the rebuild frequency from a carrier of 10 kHz.One of the effective ways to solve the problem of matching the impedances of the diodes and the load in the microwave range is to use waveguide-coaxial lines with the parameters: D2 = 1 mm, D1 = 0.5 mm, n = 2, a = 1.6 mm, b = 0 , 8 mm, Lp = 0.25λ, W0k = 42 Ohm, Rp = 0.06 Ohm, W01 = 250 Ohm.Analysis of the results shows that the criticality of the adder setting to obtain the maximum efficiency decreases with decreasing Rap and increasing N. The increase in the summation efficiency with increasing N is due to the need to reduce the load resistance. This feature of the considered scheme significantly distinguishes it from other known schemes in which the summation efficiency decreases with increasing N. To determine the number of diodes providing total power within 250 mW at frequencies 141 ... 143 GHz, numerical calculations were performed for the diode parameters 2A762A: operating frequency range f = 140 ... 145 GHz, rated power = 0.09 W, operating current I0 = 150 mA, operating voltage U0 = 12 V, Rs = 0.5 Ohm, Rp = 0.06 Ohm, C = 0.2 pF, p2 = 1, I0 / Ins = 4.Discussion: The results of numerical analysis showed that to meet the requirements for the radiation source in the frequency range 141 ... 143 GHz with an output power of at least 250 mW, it is possible on the basis of the power adder of a four-diode generator on LPD with OBR.